PENINGKATAN HASIL BELAJAR IPA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE STAD - Yati Yati (LPPM UNISDA, 2018)
The purpose of this study was to describe the implementation ofmodel cooperative learning type STAD and student learning outcomes in science learning material factors that cause changes in objects using the cooperative learning STAD typemodel. This research is a classroom action research conducted through 2 cycles with each cycle of the stages is planning, action, observation and reflection. The results showed that the learning outcomes of students in science learning light material usingmodel cooperative learning type STAD in class VI has increased each cycle, this can be seen from the level of learning completeness of students per cycle that is in pre cycle with KKM 70 students pre cycle there are 8 students or 40% who completed, then experienced an increase in the first cycle that there were 12 students or 60% and in cycle II there were 18 students or 90%, while the learning activeness of students in cycle I was 12 students or 60% and in cycle II there 16 students or 80%, the results are according to the indicators specified.